Climate variability and farm inefficiency: A spatial stochastic frontier analysis of Senegalese agriculture - K. Christophe Adjin; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
This paper aimed to analyse Senegalese farmers' technical efficiency in the context of climate variability and spatial heterogeneity. To achieve this, firstly using simulated data, we evaluated the newly developed spatial stochastic frontier estimation technique based on skew-normal distributions. Secondly, using cross-sectional survey data we conducted an empirical analysis for 4423 Senegalese farm households. Simulation results show that the estimation approach used is appropriate and produces consistent results with large sample sizes, although it might suffer from a "starting values" problem. Empirical findings reveal that agricultural production in Senegal mostly depends on the allocated area and it is highly affected by climatic factors such as rainfall and temperature. Moreover, within a radius of 4 km, the technical efficiency of farms appears to be significantly affected by unobserved spatial features. Furthermore, this farm's technical efficiency can on average be increased by 20%, when accounting for spatial heterogeneity.
urn:nbn:de:gbv:8:3-2021-00298-3
Keywords: Q54; C21; D24; 330; Climate variability; Farm efficiency; Spatial heterogeneity; Senegal